Buah yang Lebih Berharga daripada Emas dan Perak: Kajian Eksegetis atas Amsal 8:19 dan Yohanes 15:4-5 - Jie, Marcelino Bramantyoko (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2025)
Abstract This study is a Biblical study that examines Proverbs 8:19 and John 15:4-5. The text Proverbs 8:19 speaks of the fruit of wisdom which is more precious than gold and silver. The text John 15:4-5 speaks of Jesus as a vine, whoever abides in Him will bear much fruit. This study uses the exegesis method. The library sources in this study are the Indonesian Holy Bible published by LAI and commentary books. This study found that the fruit referred to in the text Proverbs 8:19 is answered in John 15:4-5. By staying with Jesus, a person also lives in His love. The disciples were sent to share love among themselves and also with others. That love invites everyone to take an active part in it. By loving each other, they became disciples of Jesus because they had shown the Father's love to the world. This is the fruit of love that is more valuable than gold and silver. This precious fruit has implications for human life, especially for the life of religious communities in building communities based on love.